Peran Konservasi Sumber Daya Air dalam Pembangunan Ekonomi, Sosial, dan Lingkungan Berkelanjutan - Andi Setyo Pambudi; Bambang Pramujo (Bulletin of Community Engagement, 2025)
Water resource conservation is vital for supporting sustainable development in Indonesia, encompassing economic, social, and environmental dimensions. Climate change, urbanization, and environmental degradation have contributed to a growing water crisis, threatening the availability and equitable distribution of water across regions. This study aims to: (1) identify water conservation issues impacting the sustainability of key sectors, (2) evaluate the role of water conservation in supporting economic development, enhancing social welfare, and protecting the environment, and (3) propose strategic policy recommendations for integrating water conservation into sustainable development efforts. Using a qualitative method approach based on literature review and descriptive-critical analysis, this study links water conservation practices with sustainable development indicators. The findings reveal that water conservation improves economic efficiency, supports food security, tourism, and industry. In the social dimension, water conservation enhances access to clean water, public welfare, and health. Environmentally, water conservation preserves ecosystems, reduces disaster risks, and contributes to climate change mitigation. The study recommends strengthening water conservation regulations, developing green infrastructure, adopting water-saving technologies, and fostering cross-sectoral collaboration. By integrating water conservation into national development policies, Indonesia can achieve sustainable water resources management that optimally supports economic, social, and environmental development.